EXPERIMENTALLY-STATISTICAL MODEL OF CLADDING LAYER FORMATION PROCESS ON SLIDE-WAYS - N. N. Maksimchenko (Наука и техника)
The developed experimentally-statistical model of the cladding composite layer formation process on slide-ways allows to operate technological modes of cladding by flexible instrument (CFI) in order to obtain the set properties of a coating (thickness, continuity, adhesion strength).The established optimum technological modes of CFI process providing formation of continuous, strongly adhered to a basis composite coatings of the required thickness have been used for applying coatings on working surfaces of slide-ways of metal-cutting machine tool beds that has allowed to lower friction factor in coupling on the average by 1.3–1.7-fold and to improve uniformity of slow moving of machine tool units by 1.74-fold in comparison with slide-ways without a coating.